New Commentaries on Ibn Al-Arabi's Fusus al-Hikam: A Comparative Study - Lohlker, Rüdiger (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2023)
One of the key concepts of Sufism as localized or indigenized Islamic wisdom in Asia is compassion (rahma). The school of the Oneness of Being (Wahdat al-Wujud) provides valuable examples for this concepts, esp., in the commentaries on the treatise of Fusus al-Hikam by Ibn al-‘Arabi. In particular, the chapter on the prophet Zakariyya demonstrate the reflection on the concept of mercy in the school of the Oneness of Being. The indigenization of this Sufi tradition is based on these commentaries that has been of utmost importance for the school of the Oneness of Being. The article analyzed some of these commentaries in the light of this localization process. Commentaries that emerged in and around the Indian Ocean, e.g., Al-Qāshānī, Jāmī, and Ilāhābādī, were selected. They can be considered part of the local wisdom in the Asiatic realms. The current article found the idea of indigenization of key concepts of Islamic spirituality in Muslim communities, particularly through Ibn ‘Arabi’s work.